Republic of Kosovo : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that growth in Kosovo has proven relatively resilient and stronger than in its western Balkan neighbors, averaging slightly more than 3 percent over the last five years. Steady remittances from the diaspora living in advanced European economies continue to be a key driver of growth, supporting as they have private consumption and investment. Medium-term growth prospects of some 3.5 percent per year, while reasonable, are not strong enough to steadily lift incomes towards regional standards, or to create enough jobs in a country with very high unemployment. Kosovo's banks remain liquid, well capitalized, and profitable. Nonperforming loans ratios are slightly elevated at 8.4 percent, but are stable and fully provisioned.